The connectivity and the static-cost-effective analysis of a shifted completely connected network - Ali, Mohammed N.M.; Rahman, M.M. Hafizur; Abubakar, Adamu; Behera, Dhiren K.; Inoguchi, Yasushi (Inderscience, 2019)
At the current time, finding an alternative computing device with extreme computation power is the main concern of the research community. Therefore, building a computer device able to execute extremely difficult calculations in a short period of time is required. Presently, the massively parallel computer (MPC) systems are considered the highest computing devices, and the existence of these systems is important to execute many operations in many sectors such as engineering and science. These devices are built based on an internal network called interconnection network has a particular design represented by the network topology. The cost of these networks is influenced highly by the price of the processing elements (PEs) and the communication links. Thus, the design of these topologies has a crucial impact on the network cost and performance. In this paper, we have proposed a new design of topology for the MPC systems; this topology has been evaluated statically in previous work, and it showed good results. Therefore, in this paper, we will focus on analysing the cost effectivity of this network to examine if it is a cost-beneficial network before going to the implementation step to assure that the profit of this network deserves the cost.